A combined aeroelastic‐aeroacoustic model for wind turbine noise: verification and analysis of field measurements. Issue 8 (3rd March 2017) - Bertagnolio, F.; Madsen, H. Aa.; Fischer, A.
Abstract: In this paper, semi‐empirical engineering models for the three main wind turbine aerodynamic noise sources, namely, turbulent inflow, trailing edge and stall noise, are introduced. They are implemented into the in‐house aeroelastic code HAWC2 commonly used for wind turbine load calculations and design. The results of the combined aeroelastic and aeroacoustic model are compared with field noise measurements of a 500 kW wind turbine. Model and experimental data are in fairly good agreement in terms of noise levels and directivity. The combined model allows separating the various noise sources and highlights a number of mechanisms that are difficult to differentiate when only the overall noise from a wind turbine is measured. Copyright © 2017 John Wiley & Sons, Ltd.